Interest in Money Waqf: Study on the Determinants of Money Waqf among Muslims in Palembang - Afifah, Arta Amaliah Nur; Syatibi, Ibi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Purpose: This study tests the influence of knowledge, level of education, religiosity, socialisation, and income on the interest in waqf money in the Muslim community in Palembang. Design/Method/Approach: This study uses the SmartPLS 3.3.9 application and the Structural Equation Modelling (SEM) model approach as a quantitative research methodology. It uses questionnaire data with the criteria of Muslim respondents in Palembang who have an income and have never received money from a waqf. The sample size was determined based on Roscoe’s theory, which is at least 10 times the number of variables studied, so the minimum number of respondents is 60. Findings: Based on the results of this study, it was found that the variables of knowledge and religiosity did not have a significant effect, with a p-value greater than the significance level of 0.05. However, the variables of education, socialisation, and income significantly affect the interest of the Palembang city Muslim community in making money waqf in BWI South Sumatra Province. This proves that the money waqf in Palembang is greatly influenced by several factors, with a p-value of less than the significance level of 0.05. Originality/Values: The main contribution of this study is to provide a survey that is needed periodically through education to the Muslim community of the city of Palembang, so that it becomes a comprehensive study that can increase the public’s interest in doing money waqf.